In and Out of the Bursa—The Role of CXCR4 in Chicken B Cell Development - Nagy, Nandor; Busalt, Florian; Halasy, Viktoria; Kohn, Marina; Schmieder, Stefan; Fejszak, Nora; Kaspers, Bernd; Härtle, Sonja (Frontiers in Immunology, 2020)
In contrast to mammals, early B cell differentiation and diversification of the antibody repertoire in chickens do not take place in the bone marrow but in a specialized gut associated lymphoid tissue (GALT), the bursa of Fabricius. During embryonic development, B cell precursors migrate to the bursa anlage, where they proliferate and diversify their B cell receptor repertoire. Around hatch these diversified B cells start to emigrate from the bursa of Fabricius and populate peripheral lymphoid organs, but very little is known how the migratory processes are regulated. As CXCL12 (syn. SDF-1) and CXCR4 were shown to be essential for the control of B cell migration during the development of lymphoid tissues in mammals, we analyzed expression and function of this chemokine/chemokine-receptor pair in the chicken bursa. We found a strong variation of mRNA abundance of CXCL12 and CXCR4 in different stages of bursa development, with high abundance of CXCL12 mRNA in the bursa anlage at embryonic day 10 (ED10). In situ hybridization demonstrated disseminated CXCL12 expression in the early bursa anlage, which condensed in the developing follicles and was mainly restricted to the follicle cortex post-hatch. Flow cytometric analysis detected CXCR4 protein already on early B cell stages, increasing during bursal development. Post-hatch, a subpopulation with the hallmarks of emigrating B cells became detectable, which had lower CXCR4 expression, suggesting that downregulation of CXCR4 is necessary to leave the CXCL12-high bursal environment. In vivo blockade of CXCR4 using AMD3100 at the time of B cell precursor immigration strongly inhibited follicle development, demonstrating that CXCL12 attracts pre-bursal B cells into the bursal anlage. Altogether, we show that CXCL12 and its receptor CXCR4 are important for both populating the bursa with B cells and emigration of mature B cells into the periphery post hatch, and that CXCR4 function in primary B cell organs is conserved between mammals and birds.